Tractive performance of a designed and developed segmented rubber tracked vehicle on Sepang peat terrain during straight motion: theoretical analysis and experimental substantiation - Rahman, Mohammed Ataur; Yahya, Azmi; Zohadie, Mohd.; Ahmad, Desa; Wan Ismail, Wan Ishak (Inderscience Enterprises Ltd., 2006)
The vehicle field tests were conducted on three different types of peat terrains: terrain type I, terrain type II and terrain type III with two loading conditions at travelled speeds of 6 km/h and 10 km/h. The different tractive efforts of the vehicle were found during field testing due to the hydrodynamic effect, different cohesiveness and the internal frictional angle. The significant difference of the vehicle slippages were found due to the variation of the moisture content of the terrain. The least variability between the measured data over the predicted data substantiates the validity of the mathematical model.